Vascular Graft Update: Safety and Performance 1986
DOI: 10.1520/stp33296s
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Prostheses: The Need for Standards—Historical and Surgical Perspectives

Abstract: The historical and surgical perspectives with respect to standards for vascular prostheses are summarized under three headings: (1) device legislation tracing the activities of the Food and Drug Administration (FDA), ASTM, and International Organization for Standardization (ISO) from 1964 culminating in the present Medical Device Legislation as signed in 1976; (2) scientific community involvement via the media of ASTM, American Society for Artificial Internal Organs (ASAIO), Association for the Advancement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There are distinctive advantages to the use of pigs in that they share similar anatomic and physiologic characteristics with humans particularly pertaining to the cardiac and vascular systems 25 . Classic animal experimental data reported by Wesolowski 18 on growing pigs weighing 20-39 kg formed the benchmark for graft research as implantation data of three months in growing pigs in terms of healing patterns and characteristics were noted to be equivalent to three years in man. Hence, we chose pigs as the animal model in addition to the fact that preclinical trial of the standard uncoated graft was also successfully completed in pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are distinctive advantages to the use of pigs in that they share similar anatomic and physiologic characteristics with humans particularly pertaining to the cardiac and vascular systems 25 . Classic animal experimental data reported by Wesolowski 18 on growing pigs weighing 20-39 kg formed the benchmark for graft research as implantation data of three months in growing pigs in terms of healing patterns and characteristics were noted to be equivalent to three years in man. Hence, we chose pigs as the animal model in addition to the fact that preclinical trial of the standard uncoated graft was also successfully completed in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Three groups were assigned explantation to study healing characteristics at 2, 12 and 26 wk with six animals each as test and three each as control. Weslowski's experiments showed that healing pattern in pigs over three months was equivalent to three years in man 18 . In addition, large animal like pig posed significant supportive and financial impact, limiting the number.…”
Section: Methodsmentioning
confidence: 99%
“…Classic animal experimental data reported by Adam Wesolowski delineated pigs as the most suitable model for in vivo experiments10. His original work on growing pigs weighing 20-39 kg formed the benchmark for graft research as implantation data of three months in growing pigs in terms of healing patterns and characteristics were noted to be equivalent to three years in man.…”
Section: Discussionmentioning
confidence: 99%